Chemical synthesis and functionalization of magnetic particles for the applications in microwave attenuation - Yang, Zhihong (2015)
Nowadays, with the rapid development of wireless communications and high-frequency circuit devices in gigahertz range, electromagnetic interference (EMI) has became a serious problem. Currently, the electromagnetic attenuation (EMA) materials are requested to have not only strong wave attenuation and wide frequency bands, but also small thickness and lightweight. The most commonly used attenuation materials are spinel and hexagonal ferrites and magnetic metal and alloys. Compared with ferrites, the magnetic metal and alloys have the larger saturation magnetization. However, their high conductivity would decline their EM attenuation properties in the gigahertz range that is due to the eddy current losses and the poor impedance matching between the the materials and free space. On the other hand, for some specific applications which require the lightweight, the large densities of common magnetic metal (~ 7g/cm3) and ferrite (~ 5 g/cm3) may inhibit their applications in this purpose. In this PhD study, some ferrite and their metallic cournterparts with different morphologies have been synthesized by employing many different kinds of chemical methods including sol-gel, molten-salt and hydrothermal process. These ferrites and metals with specific morphologies are expected to be used as new types of microwave attenuation materials with broad bandwidth and lightweight as compare to the conventional ones. Firstly, through a simple sol-gel approach, NiCuZn ferrite nanoparticles have been coated on the commercial sendust flakes. This NiCuZn ferrite layer can remarkably reduce the permittivity value of pure sendust flakes. In that way, a better impedance matching condition can be achieved and the reflection loss is exceeding -20 dB at 1.4 GHz with a thickness of 6 mm while the reflection loss for the uncoated Sendust flakes could not reach -10 dB at the same sample thickness. Secondly, plate-like W-type barium ferrite particles with high aspect ratio (diameter/thickness) of ~35 have been prepared by a molten salt method combined with a sol-gel process. Owing to the low demagnetization factor Nd for the flaky shape, silicon resin composites filled with these plate-like particles show a broad attenuation bandwidth. Thirdly, in order to exploit the materials for the light weight purpose, three types of ferrite and their metal counterparts with hollow or mesoporous structures have been synthesized through the solvothermal process. These hollow or mesoporous structures can effectively decrease the densities of the conventional ferrites and metals, hence the usage/thickness of silicon resin composite can be significantly reduced. Meanwhile, the SiO2 insulating layer coating on the porous metal particles can not only maintain the porous structures and prevent them from oxidation, but also cut off the polarization between particles and achieve a better impedance match. In that way, they are very promising as a strong-attenuation and light-weight electromagnetic wave attenuation material.